The Use of Synbiotics to Prevent IMNV and Vibrio harveyi Co-Infection in Litopenaeus vannamei - ADNI OKTAVIANA; . WIDANARNI; MUNTI YUHANA (Bogor Agricultural University, Indonesia, 2014)
This study evaluated the effects on viral immune responses and bacterial co-infection, of different feeding frequencies of a synbiotic supplemented diet given to Pacific white shrimp (L. vannamei). A synbiotic-supplemented diet was formulated from probiotic Vibrio alginolitycus SKT-bR and prebiotics from sweet potato (Ipomoea batatas L.) oligosaccharide. Pacific white shrimp were fed the synbiotic diet at different frequencies, i.e. daily (P1), twice a week (P2), and once a week (P3) for a 30 day pre-challenge test. After the 30 day feeding period, the shrimps were challenged by intramuscular injection of Infectious Myonecrosis Virus (IMNV) and Vibrio harveyi. The results showed that shrimp treated with a synbiotic-supplemented diet showed significantly higher growth performance than control groups (P<0.05). Shrimp treated under regime P1 showed the highest values for phenoloxidase (PO) and respiratory burst (RB) parameters compared to shrimp given the other treatments. Following the challenge test, higher survival rate were seen in the P1 treatment group, in comparison to the positive control, and the P1 treatment group showed the highest values in total haemocyte count (THC), PO, and RB.